2018
DOI: 10.1080/15548627.2018.1474312
|View full text |Cite
|
Sign up to set email alerts
|

ROS is the major player in regulating altered autophagy and lifespan insin-3mutants ofC. elegans

Abstract: SIN3, a transcriptional corepressor has been implicated in varied functions both as transcription activator and repressor. Recent studies associated Sin3 with the macroautophagic/autophagic process as a negative regulator of Atg8 and Atg32. Though the role of SIN3 in autophagy is being explored, little is known about the overall effect of SIN3 deletion on the survival of an organism. In this study using a Caenorhabditis elegans sin-3(tm1279);him-5(e1490) strain, we demonstrate that under in vivo conditions SIN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
48
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(50 citation statements)
references
References 90 publications
2
48
0
Order By: Relevance
“…4 B). In many studies, mROS have been implicated in autophagy [18] , [19] , [20] . Consistent with these studied, 5-ALA-PDT increased LC3-II/β-actin protein level, which was significantly attenuated after treatment with Mito-TEMPO ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…4 B). In many studies, mROS have been implicated in autophagy [18] , [19] , [20] . Consistent with these studied, 5-ALA-PDT increased LC3-II/β-actin protein level, which was significantly attenuated after treatment with Mito-TEMPO ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Given that ROS can also affect autophagy level, to further determine the effects of H 2 O 2 on MSC autophagy, we examined LC‐3B II/I ratio and p62 expression in the Rapa + H 2 O 2 co‐treatment (1.0, 10.0 and 100.0 μmol/L) groups. The results showed that LC‐3B II/I ratio increased and p62 expression decreased in the Rapa and Rapa + H 2 O 2 co‐treatment groups relative to those in the Control and D‐gal Control groups ( P < .01, Figure A,B).…”
Section: Resultsmentioning
confidence: 99%
“…To further explore the mechanism of toxicity of SiO 2 NPs, we examined the expression levels of oxidative stress-related genes. The five nematode sod genes (sod-1, sod-2, sod-3, sod-4, sod-5) are homologs of mammalian cytoplasmic, mitochondrial, and extracellular superoxide dismutase (SOD1, SOD2, SOD3), and the three nematode ctl genes (ctl-1, ctl-2, ctl-3) are homologs of mammalian cytoplasmic and peroxisomal catalase (CAT) (Sharma et al, 2018). The sod genes are involved in superoxide dismutase and protein homodimerization activity, and the ctl genes are related to catalase activity (Zelko et al, 2002;Song et al, 2014).…”
Section: Discussionmentioning
confidence: 99%